2012
DOI: 10.1017/s136898001200345x
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver food behaviours are associated with dietary intakes of children outside the child-care setting

Abstract: Objective: To evaluate whether food behaviours of parents are associated with children's dietary intakes outside the child-care setting, and to compare children's dietary intakes at home with foods and beverages consumed when they are at child-care centres. Design: In 2005-2006, a survey was completed by parents of at least one child between 3 and 5 years old who attended group child-care centres. Surveys about nutrition practices were completed by centre directors. Research assistants observed foods and bever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 49 publications
0
27
0
1
Order By: Relevance
“…A recent study 29 described that the food offered to children at home is less healthy than those offered at child-care centres in the US and among the 16 child-care centres included in the study, none reported providing soft drinks to children. 32 In the present study, 32% of children at 2-years-of-age had a daily consumption of energy-dense foods (soft drinks, sweets, cakes or salty snacks), this number was low compared with those reported by studies in other developed countries.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study 29 described that the food offered to children at home is less healthy than those offered at child-care centres in the US and among the 16 child-care centres included in the study, none reported providing soft drinks to children. 32 In the present study, 32% of children at 2-years-of-age had a daily consumption of energy-dense foods (soft drinks, sweets, cakes or salty snacks), this number was low compared with those reported by studies in other developed countries.…”
Section: Discussionmentioning
confidence: 95%
“…The majority of research within educational institutions has been from intervention studies; seven strategies (3,39,46,54) were identified compared with two exposures from observational studies (53) . A total of six exposures have been examined within the community setting, all from observational research (26,27,29,41,48,51) . Studies were also mapped by environment type (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…restaurants, clubs, fast food, takeaway) (57) . The frequency of meals away from home, a communitybased socio-cultural influence, was significantly associated with higher children's intake of discretionary choices (60 % of studies) (26,27,29,41) . This highlights an opportunity for interventions to evaluate strategies to support parents at times when meals are consumed away from home; for example, healthy options guide or skills-based resources of nutritious foods to take when likely to consume foods away from home.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there is no evidence evaluating whether orders of adult menu items are healthier when the healthy menu intervention is targeted to the children’s menu. Yet adults can serve as role models for healthier choices in restaurants [ 12 ], can help establish norms around healthy dietary practices [ 13 , 14 , 15 , 16 ], and engage in other food-related parenting practices that can promote healthier choices in restaurants for children [ 16 , 17 ]. Restaurant meals are also associated with poorer overall dietary quality and chronic disease risk in adults [ 2 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%